Cutting surfaces and applications to periodic points and chaotic-like dynamics - Pireddu, Marina; Zanolin, Fabio (Topological Methods in Nonlinear Analysis, 2007)
In this paper we propose an elementary topological approach which unifies and extends various different results concerning fixed points and periodic points for maps defined on sets homeomorphic to rectangles embedded in euclidean spaces. We also investigate the associated discrete semidynamical systems in view of detecting the presence of chaotic-like dynamics.